PELATIHAN PENGGUNAAN DOMPET DIGITAL BAGI MASYARAKAT DESA BANTARJAYA - Veronika Dwi Islami; Kurniawati Mulyanti; Yuha Nadhirah Qintharah (Universitas Islam 45 Bekasi, 2023)
The implementation of this community service involves the community in Bantarjaya Village. The lack of public knowledge about the use of technology in everyday life, especially digital wallets, makes people in Bantarjaya Village less able to utilize digital technology with online transactions. After the Covid-19 pandemic, people switched to using online media as a tool for transactions using applications to avoid direct contact. Of course this makes people have to adapt to the application as a new habit in transactions. The digital wallet technology currently available has not been fully used by the whole community. One possible obstacle is the emergence of a feeling of laziness and ignorance, or it could also be caused by a sense of public concern about administrative costs. In fact, existing digital wallet accounts can use cellphone numbers and are free of administration fees. Banks that are part of Himbara (State Owned Bank Association) have collaborated with E-Wallet Providers in Indonesia with all the convenience and security of transactions. Therefore this community service is carried out with the aim of developing human resources in utilizing digital technology by using digital wallets as a transaction tool.